Max-flow based load-balancing channel assignment algorithm for wireless mesh network - Tao-shen LI; Ya-huan WEI; Zhi-hui GE (Tongxin xuebao, 2012)
In view of the interference problem between channels and traffic flow load-balancing in wireless mesh networks,an objective optimization function for balancing network load was defined,and a load-balancing channel assignment algorithm based on maximum flow was proposed.In the algorithm,the links with larger flow load had a priority to allocate more bandwidth.The purpose of doing it was to make the key links could support larger flow load,balance the channels,reduce packet loss rate and delay in the network.Simulation results show that the algorithm can balance the network load and obtain better performance even in the heavier load network.